IBR-DTN: A lightweight, modular and highly portable Bundle Protocol implementation - Schildt, Sebastian; Morgenroth, Johannes; Pöttner, Wolf-Bastian; Wolf, Lars (Electronic Communications of the EASST, 2011)
In this paper we present IBR-DTN, a lightweight, modular and portable Bundle Protocol implementation and DTN daemon. IBR-DTN is especially suited for embedded platforms, which allows to leverage the benefits of a fully compliant Bundle Protocol daemon in cost sensitive distributed sensing applications. We line out IBR-DTN's extensible software architecture and introduce the modules included in the standard IBR-DTN distribution. To give an impression of the performance that can be expected when using IBR-DTN, we perform a series of benchmarks and compare the outcome with DTN2 performance, the reference implementation of the Bundle Protocol.